Developing a multilingual identity in the languages classroom: the influence of an identity-based pedagogical intervention. Issue 4 (4th July 2021) - Forbes, Karen; Evans, Michael; Fisher, Linda; Gayton, Angela; Liu, Yongcan; Rutgers, Dieuwerke
ABSTRACT: It is natural to assume the languages classroom to be a key site for the construction of learners' linguistic and multilingual identities. Yet, an underlying assumption exists that this will occur regardless of whether teachers explicitly raise learners' awareness about the nature of language and how language is implicated in their lived experience. We argue, therefore, that a new dimension of languages pedagogy is necessary in order for learners to understand their own and others' linguistic repertoires (whether learned in school, at home or in the community) and so to recognise their agency in being able to claim a multilingual identity. In this paper, we present a rationale for and explore the effect of an innovative programme of participative multilingual identity education which was implemented by teachers in languages classrooms across four secondary schools in England over the course of one academic year. Data were collected through questionnaires administered before and after the intervention and sought to trace the formation of students' multilingual identity. Evidence from this study suggests that while more traditional interventions focusing on raising awareness about the benefits of languages can be beneficial, effects can be enhanced by an additional 'identity' element, i.e. actively promoting reflexivity.